Overcoming Stress on Psychology Study Program Students at the University of Muhammadiyah Sidoarjo who are Compiling Thesis during the Covid-19 Pandemic: Mengatasi Stres pada Mahasiswa Prodi Psikologi Universitas Muhammadiyah Sidoarjo yang Sedang Menyusun Skripsi di Masa Pandemi Covid-19 - Khotimah, Isnaini Khusnul; Paryontri, Ramon Ananda (Universitas Muhammadiyah Sidoarjo, 2022)
In this study, the aim of this study was to identify stress coping strategies carried out by students of the Psychology Study Program at the University of Muhammadiyah Sidoarjo in compiling a thesis during the Covid-19 pandemic. The research subjects consisted of three active students from the psychology study program at Muhammadiyah University of Sidoarjo who were preparing a thesis using purposive sampling technique. This study uses a qualitative phenomenological research method, with data collection techniques using a semi-structured interview process. The data analysis technique used the model of Miles and Huberman (1985). The results of this study explain that the use of stress coping, both problem focus coping and emotional focus coping, has its own role for students who make efforts to minimize or eliminate negative things, due to pressure that makes them feel threatened, uncomfortable, resulting in stressful conditions, both both are able to help in overcoming problems effectively, besides the importance of paying attention to several factors supporting the success and effectiveness of a coping. Basically a problem that occurs when someone is in the process, of course they have various ways of dealing with these problems in order to be able to resume what has been done and to be able to achieve the goals that have been set and go to the next stage.